2021
DOI: 10.1007/s13201-021-01479-1
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration and mineralization of a textile azo dye using a hybrid UV/O3/SBR process

Abstract: Most synthetic dyes are toxic and hardly biodegradable compounds that enter the environment mainly through the discharged of non-treated textile industry effluents. The present study investigated the removal of the textile monoazo dye Reactive Red 198 (RR-198) from aqueous solutions using the ultraviolet light and ozonation alone and in combination (i.e., UV/O3) followed by a Sequencing Batch Reactor (SBR). The pH (5 ≤ pH ≤ 9) and dye initial concentration (50–300 mg/L) parameters were optimized in the ozonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The O 3 /UV system enhanced the decomposition of ozone molecules and produced more free radicals. [43] Therefore, the highest removal efficiency occurs with photo-oxidation (O 3 /UV) processes, followed by O 3 and photolysis (UV) systems. The results also showed that the O 3 and UV processes were synergistic with each other, reaching a maximum at a reaction time of 20 minutes, equivalent to 100%.…”
Section: Effect Of the Time On Uv/o 3 /Pms Processmentioning
confidence: 99%
“…The O 3 /UV system enhanced the decomposition of ozone molecules and produced more free radicals. [43] Therefore, the highest removal efficiency occurs with photo-oxidation (O 3 /UV) processes, followed by O 3 and photolysis (UV) systems. The results also showed that the O 3 and UV processes were synergistic with each other, reaching a maximum at a reaction time of 20 minutes, equivalent to 100%.…”
Section: Effect Of the Time On Uv/o 3 /Pms Processmentioning
confidence: 99%
“…[45] The results obtained by Mahdizadeh et al to remove textile monoazo dye Reactive Red 198 and TOC using the hybrid UV/O 3 /Sequencing Batch Reactor (SBR) system showed that the highest discoloration percentage (97.5%) and TOC removal (86.3%) was found. [43] Fig7. The effect of the time of the reaction efficiency of the UV/O 3 /PMS process.…”
Section: Effect Of the Time On Uv/o 3 /Pms Processmentioning
confidence: 99%
“…Post-production wastewater from the textile, tanning or paper industries may contain significant amounts of dyes. Industrial dyes are usually of synthetic origin, feature a complicated chemical structure, and are highly stable, which makes them sparingly biodegradable [ 1 ]. Due to the high color intensity and ease of application, anionic reactive dyes are most often used in dyeing processes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%